Elevate Company's Social Media as a Diversity, Equity, and Inclusion Platform: Multi Cases Study to Digital Technology Companies - Putriani, Intansari; Aras, Muhammad (Journal of World Science, 2022)
Introduction: Social media platforms have allowed people of different backgrounds to reach out and share what they know, giving us a glimpse of people's lives worldwide. By doing this, diversity and inclusion are promoted and celebrated. It is critical to our success as a company. In contrast to traditional diversity programs, diversity and inclusion programs concentrate a higher emphasis on developing individual values as opposed to teaching soft skills. Social media platforms have enabled people from all backgrounds to reach out and share their knowledge, giving us a window into people's lives worldwide. Diversity and inclusivity are therefore fostered and celebrated. Method: This study uses a qualitative approach to understand the concept of diversity, equity, and inclusion (DEI) in the startup context with Meta, TikTok, and Twitter objects. Result: The result showed that, during the COVID-19 epidemic, the social media presence of Meta, Twitter, and TikTok had expanded significantly, as seen results. This modification reflects the urgent requirement to connect with candidates in a quickly evolving environment. It is also the outcome of the growing significance of social media presence in a society that is becoming increasingly digital. Conclusion: Social media also plays a crucial role in promoting diversity by providing a platform for representation and opportunities for different voices to speak to a broader audience. These platforms allow us to represent ourselves and our diverse cultures as we'd like to be seen by others.